Evaluation of Molecular Parameters: Viscosity Variation Method - MURTHY, M.B.R.; DAYASAGAR, B.S.; PATIL, R.L. (Asian Journal of Chemistry, 2010)
A new method of evaluating dipole moment of a polar molecule in a non-polar solvent by viscosity variation is proposed. This method needs dilute solution of only one concentration and will be quite useful to evaluate molecular parameters of newly synthesized compounds.